LAYOUT REDESIGN OF CONTAINER SHAKIGNG FIELD AT PT. XYZ - Muhammad Nawir; Andi Pawennari; Ahmad Padhil; A. Dwi Wahyuni. P; Muhammad Dahlan; Takdir Alisyahbana Alisyahbana; Rahmaniah Malik (Journal of Industrial Engineering Management, 2022)
The Layout of the Field Layout Stacking containers is an important thing to consider because it can affect the effectiveness of the loading and unloading process in the field by arranging the Layout of the facilities in the stacking field in the Yard Layout including the Rubber Gantry Crane (RTG) and the arrangement of the lane Head Truck. So, it is necessary to research determining the Layout of containers. The design that will be made will affect the distance the head truck travels to transport containers from the dock. In several studies, two types of determined, Layout have been container namely Parallel Layout where the containers are arranged parallel to the pier, and Perpendicular Layout where the containers are arranged Perpendicular to the pier. Container terminal Makassar New Port using Parallel Layout. To increase the productivity of the loading and unloading process, an analysis of the arrangement of the stacking field is carried out. From the results of the research, the farthest travel distance is 1,048 m, with a total travel distance of 729,269 m with a fuel cost of Rp. 1,144,952 in the initial Layout (Parallel Layout), with the Perpendicular Layout, the farthest travel distance is 353.7 m with a total travel distance of 473,533 m, and the use of materials burn 743,446.8 m